Effect of Hip Abductor Muscle Fatigue on Static and Dynamic Balance in Elderly Women - Farideh Babakhani; Kobra Oladghobadi; Farajollah Fatahi (University of Social Welfare & Rehabilitation Sciences, 2016)
Objectives: Postural control is the act of maintaining and restoring a better state of balance and proper biomechanics structure in limbs and different parts of the body. Such proper structure exists in two forms namely static and dynamic. Fatigue is one of the factors that affect the postural control and body stability. The purpose of this study was to examine the effect of hip abductor muscle fatigue on the static and dynamic balance in elderly women. Methods & Materials: The participants of this study included 25 elderly and healthy women without any disability (60.24±8.5 years old, weight: 60.58±9.54 kg, height: 153.42±7.65 cm). In the first session, the participants underwent static and dynamic balance tests in the normal condition (without fatigue). In the second session, at first, they participated in the hip abductor muscle fatigue protocol followed by static and dynamic balance tests. In addition, t-test was used to compare the results before and after the fatigue. Results: The results indicated that the hip abductor muscle fatigue protocol led to a significant reduction in test scores of balance tests, which included static and dynamic balance. Also, a significant difference was observed between static and dynamic balance before and after fatigue. Overall, the measure of the effect of fatigue protocol was notable in both the tests (P<0.05). Conclusion: Reduction in the scores of static and dynamic balance tests showed that the hip abductor muscle fatigue caused an increase in the amount of damage and length of disability in elderly women.